2020
DOI: 10.1080/07388551.2020.1731413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mixing intensity and duration on biogas production in an anaerobic digester: a review

Abstract: This paper is a critical evaluation of the effect of mixing on biogas production rates in an anaerobic digester. Mixing plays a prominent role in determining the efficiency of the anaerobic digestion process. This review analyzes the miscellaneous effects of mixing (on the microbial community, methane content and volatile fatty acids) at various mixing intensities and during different stages of the digestion process. Intermittent mixing (mixing at intervals) seems preferable in terms of the quality and quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Generally, mixing in the anaerobic zone is essential as it promotes the distribution of substrates and microorganisms thoroughly within the digester in achieving homogeneity. Mixing can also overcome the rheological behaviour of the nature of slurry which poses complications in attaining turbulence while also forming dead zones inside the digester 13 Figure 4 depicts the capability of IAAB in treating POME that exhibits a large range of COD. It can be observed that the anaerobic COD removal efficiency somewhat increases as the strength of the wastewater increases.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, mixing in the anaerobic zone is essential as it promotes the distribution of substrates and microorganisms thoroughly within the digester in achieving homogeneity. Mixing can also overcome the rheological behaviour of the nature of slurry which poses complications in attaining turbulence while also forming dead zones inside the digester 13 Figure 4 depicts the capability of IAAB in treating POME that exhibits a large range of COD. It can be observed that the anaerobic COD removal efficiency somewhat increases as the strength of the wastewater increases.…”
Section: Resultsmentioning
confidence: 99%
“…The AD batch experiments were performed under thermophilic conditions at 55 °C ± 2. The digester content was stirred 2 min day −1 to promote bacterial growth and ensure the best performance while maintaining energy consumption as low as possible (Singh et al 2020). The biogas production was measured every day and its composition was analyzed every 2 days; the method is further described.…”
Section: Digestion Processmentioning
confidence: 99%
“…As a consequence, the scaling-up of pilot scale mixing processes is a crucial feature for maximizing current mixing and flow processes by holding all measurements within a set ratio, known as a scale-up factor [45]. Minimum periodic mixing is observed to be favorable for a successful anaerobic digestion operation [46][47][48]. Intermittent mixing with longer resting periods may result in higher biogas output and, in most situations, increased mixing time cycles have not seen much impact on biogas production, but comparable results can be produced at lower power consumption [49].…”
Section: Practical Implication Of This Studymentioning
confidence: 99%